Cringe-watching: How EduXperience’s Moralizing Does (Not) Advance Social Change (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
This paper scrutinizes the deployment of immersive media, particularly, virtual reality (VR) in the context of climate change education, focusing on the case study of EduXperience Biosphere VR (2021). The analysis challenges the assumption that such technologies inherently promote desired social trans- formations, arguing that they can also perpetuate colonialist narratives and fail to provoke meaningful action. By examining the visual strategies, sound, scripts and para-texts employed in Biosphere VR’s documentaries, the paper shows how these el- ements can reinforce problematic tropes of the so-called Global South as “the frontier.” While VR holds promise for experiential learning (especially with glitches and similar unintentional ef- fects that break down the point of view), specific forms of com- munication tend to prioritize simplistic moralizing over nuanced albeit critical engagement with complex socio-environmental issues. Drawing on critical theory in visual and spatial studies, the paper calls for further approaches to the representation of climate change, globality, space, communities, places and sites that could better prioritize social justice and models of terrestrial, reciprocal interdependence.
Keywords: Educational VR; Empathy machine; Gaze from above; Völkerschau; Ways of seeing